Huaier Induces Immunogenic Cell Death Via CircCLASP1/PKR/eIF2α Signaling Pathway in Triple Negative Breast Cancer - Li, Chen; Wang, Xiaolong; Chen, Tong; Li, Wenhao; Zhou, Xianyong; Wang, Lishui; Yang, Qifeng (Frontiers in Cell and Developmental Biology, 2022)
Triple-negative breast cancer (TNBC) is the most lethal breast cancer subtype owing to the lack of targeted therapeutic strategies. Immunogenic cell death (ICD), a modality of regulated cancer cell death, offered a novel option for TNBC via augmenting tumor immunogenic microenvironment. However, few ICD-inducing agents are currently available. Here, we showed that Trametes robiniophila Murr (Huaier) triggered ICD in TNBC cells by promoting cell surface calreticulin (CRT) exposure, and increasing release of adenosine triphosphate (ATP) and high-mobility group protein B1 (HMGB1). Co-culturing with Huaier-treated TNBC cells efficiently enhanced the maturation of dendritic cells (DCs), which was further validated via cell-based vaccination assay. In the xenograft mouse model, oral administration of Huaier led to tumor-infiltrating lymphocytes (TILs) accumulation and significantly delayed tumor growth. Besides, depletion of endogenous T cells obviously abrogated the effect. Mechanically, Huaier could elicit endoplasmic reticulum (ER) stress-associated ICD through eIF2α signaling pathway. Further studies revealed that circCLASP1 was involved in the Huaier-induced immunogenicity by binding with PKR in the cytoplasm and thus blocking its degradation. Taken together, we highlighted an essential role of circCLASP1/PKR/eIF2α axis in Huaier-induced ICD. The findings of our study carried significant translational potential that Huaier might serve as a promising option to achieve long-term tumor remission in patients with TNBC.